Prevalence and risk factors of poor sleep quality in continuous ambulatory peritoneal dialysis patients in Nanchang, Southeast China. Issue 1 (31st December 2022) - Yan, Caixia; Zeng, Chuanfei; Ma, Yujiao; Zhan, Xiaojiang; Min, Yan
Abstract: This study aimed to explore the prevalence and risk factors of poor sleep quality in patients undergoing continuous ambulatory peritoneal dialysis (CAPD) at the peritoneal dialysis center of the First Affiliated Hospital of Nanchang University. This cross-sectional study was conducted from March 2019 to December 2019. The Pittsburgh Sleep Quality Index (PSQI) was used to evaluate the sleep quality of patients undergoing CAPD. A PSQI score of ≥5 was defined as poor sleep quality, whereas a PSQI of <5 was defined as good sleep quality. Logistic regression analysis was used to analyze risk factors for poor sleep quality. In total, 456 patients undergoing CAPD were investigated. The average PSQI score was 5.0 ± 2.9. Among the participants, 46.3% had poor sleep quality, and 45.6% were female patients. The average age was 49.4 ± 13.3 years. Compared with good sleepers, poor sleepers included a higher proportion of females and calcium–phosphorus (Ca × P) product, longer dialysis durations, lower total endogenous creatinine clearance rates, less residual renal function, and lower albumin levels. Multivariate logistic regression analysis showed that a long dialysis duration, low albumin level, and high Ca × P product were independent risk factors for poor sleep quality in patients undergoing CAPD. Odds ratios (95% confidence interval) for these risk factors were 1.01 (1.00–1.02), 0.95 (0.91–1.00), and 1.02 (1.00–1.03), respectively. Interventions aimed at improving albumin and Ca × P product levels may improve quality of life for CAPD patients.